Soluble solids due to the truss position in minitomato hybrids from dwarf lines - Finzi, Rafael Resende; Marquez, Guilherme Repeza; Maciel, Gabriel Mascarenhas; Momesso, Maurício Pivetta; Pereira, Lucas Medeiros; Silveira, Aline José da (Agrarian, 2019)
On minitomatoes, the soluble solids content (SSC) is a fundamental characteristic for commercialization. Therefore, is essential to evaluate the genetic diversity among the genotypes, looking their SSC and also the SSC variation, related to the position of the cluster, mainly due to the new technologies – tomato hybrids obtained from dwarf lines. In this sense, the objective of the experiment was to evaluate the genetic variability and the influence of the cluster’s position on the SSC, in minitomato genotypes that were obtained from dwarf lines. The experiment were conducted on a greenhouse and set up in a completely randomized design, with subdivided portion of 13 hybrids x 5 cluster’s position and four replications. The SSC of the fruits were evaluated according with their position of the clusters, being the values expressed in 0Brix. The genetic diversity was obtained by multivariate analyzes, using the generalized distance of Mahalanobis, utilizing different grouping methods (UPGMA and Tocher). The hybrids performance for SSC was checked by the Scott-Knott test (p=0.005). The cluster’s position influenced on the SSC of the minitomatoes fruits and the first cluster of all hybrids that were evaluated, presented the highest SSC. Besides that, the highest 0Brix variability among the genotypes occurred when the fruits were harvested on the fifth and first cluster. Most hybrids originated from dwarf lines did not presented a reduce on 0Brix values during the harvests.